The partnership in the mental health care: an experience in psicossocial approaches and in the co-management of a mental health community service in Fortaleza/CE - Godoy, Maria Gabriela Curubeto; Viana, Ana Paula Fernandes; Vasconcelos, Kamilla Angélica G. de; Bonvini, Otorino (Saúde e Sociedade, 2012)
This is the report of the partnership experience between a nongovernmental organization that works with Mental Health and the Health Municipal Commission of Fortaleza/Ceará. This partnership has expanded several psychosocial actions as Community Therapy, Biodance, Self-Esteem Groups, courses of arts/music, massotherapy, herbal medicine therapy and other integrative practices. The co-management of a Psychosocial Center has also been articulated. This paper describes the trajectory of the nongovernmental organization, describes some of the activities offered to the population and analyses the possibilities, difficulties and challenges of the partnership that has been essayed.